Vehicle window glass
The vehicle window glass design with a non-tempered first glass plate and high Young's modulus interlayer film addresses rigidity and chipping resistance issues, enhancing structural integrity and reducing breakage in lightweight laminated glass.
Patent Information
- Application Number
- JP2021012710
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-29
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing lightweight laminated glass vehicle window designs suffer from reduced rigidity and chipping resistance due to thinner outer glass plates and the use of interlayer films with low Young's modulus, which can lead to increased breakage and reduced tensile stress resistance.
A vehicle window glass configuration with a first glass plate thickness of 1.5 mm or less, non-tempered, and an interlayer film with a Young's modulus of 2.5 MPa to 200 MPa, ensuring the second glass plate has adequate thickness and a single-layer or multilayer interlayer film structure to enhance rigidity and chipping resistance.
The solution provides lightweight vehicle window glass with improved rigidity and chipping resistance, maintaining structural integrity and reducing breakage risk.
Smart Images

Figure 0007620438000002 
Figure 0007620438000003 
Figure 0007620438000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to vehicle glazings. [Background technology]
[0002] In recent years, with the demand for lighter vehicles such as automobiles and railway cars, lighter laminated glass is also required for use as window glass for vehicles. Thus, the glass sheets used in laminated glass are being made thinner to reduce the weight of the laminated glass.
[0003] For vehicle window glass, lightweight laminated glass with a different thickness structure is often used, in which the glass sheet on the outside of the vehicle is thicker from the viewpoint of increasing resistance to small flying debris while the vehicle is moving, and the glass sheet on the inside of the vehicle is thinner from the viewpoint of reducing weight.
[0004] Patent Document 1 discloses a laminated glass having glass plates with different thicknesses and an interlayer film with a multilayer structure made of polyvinyl butyral (PVB) layers.
[0005] Furthermore, Patent Document 2 discloses a laminated glass in which a chemically strengthened glass plate is used as an outer glass plate, and the thickness of the outer glass plate is made thinner than that of the inner glass plate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2015-516934 [Patent Document 2] Patent No. 5890518 Summary of the Invention [Problem to be solved by the invention]
[0007] One of the performances required for vehicle window glass is chipping resistance. Chip resistance is an index showing the resistance to chipping and breaking when a small flying object collides with the vehicle window glass while the vehicle is running. The inventors' research has revealed that when an interlayer film with a relatively low Young's modulus is used, the rigidity of the laminated glass is reduced and the chipping resistance is reduced, making the laminated glass more likely to break when the thickness of the glass sheet on the vehicle exterior is reduced in order to reduce the weight. In addition, in order to improve the strength of the lightweight laminated glass, glass that has been subjected to a tempering treatment is sometimes used for the glass sheet on the vehicle exterior. In this case, it has been found that the chipping resistance is further reduced due to the tensile stress generated inside the glass.
[0008] In view of the above, an object of the present disclosure is to provide a lightweight vehicle window glass having excellent rigidity and chipping resistance. [Means for solving the problem]
[0009] The problem of the present disclosure is solved by the following configuration. <1> A first glass plate having an S1 surface facing the outside of a vehicle and an S2 surface opposite to the S1 surface; A second glass plate having an S4 surface facing the interior of the vehicle and an S3 surface opposite to the S4 surface; an interlayer film composed of at least one layer disposed between the first glass plate and the second glass plate and facing the S2 surface and the S3 surface; A vehicle window glass comprising: The Young's modulus of all layers constituting the intermediate film is 2.5 MPa to 200 MPa, The first glass sheet is not tempered, The first glass plate has a thickness of 1.5 mm or less. <2> The thickness of the first glass plate is 0.3 mm to 1.5 mm. <1> The vehicle window glass according to claim 1. <3> The Young's modulus of all layers constituting the interlayer film is 10 MPa to 100 MPa at 23°C. <1> or <2> The vehicle window glass according to claim 1. <4> The thickness of the second glass plate is 0.3 mm to 1.7 mm. <1> ~ <3> 13. A vehicle window glass according to claim 12. <5> The interlayer film is an interlayer film composed of one layer. <1> ~ <4> 13. A vehicle window glass according to claim 12. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a lightweight vehicle window glass having excellent rigidity and chipping resistance. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view of an example of a vehicle window glass. [Diagram 2] 1 is a schematic cross-sectional view of an example of a vehicle window glass. [Diagram 3] FIG. 2 is a schematic diagram for explaining a chipping resistance test. [Figure 4] FIG. 1 is a schematic diagram for explaining a concentric bending test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The vehicle window glass of the present disclosure includes a first glass plate having an S1 surface facing the outside of the vehicle and an S2 surface opposite to the S1 surface; A second glass plate having an S4 surface facing the interior of the vehicle and an S3 surface opposite to the S4 surface; an interlayer film composed of at least one layer disposed between the first glass plate and the second glass plate and facing the S2 surface and the S3 surface; A vehicle window glass comprising: The Young's modulus of all layers constituting the intermediate film is 2.5 MPa to 200 MPa, The first glass sheet is not tempered; The first glass plate has a thickness of 1.5 mm or less.
[0013] FIG. 1 shows a schematic cross-sectional view of an example of a vehicle window glass according to the present disclosure.
[0014] The vehicle window glass 10 in Fig. 1 has a first glass plate 1, a second glass plate 2, and an interlayer film 3. The first glass plate 1 has an S1 surface facing the outside of the vehicle and an S2 surface opposite the S1 surface. The second glass plate 2 has an S4 surface facing the interior of the vehicle and an S3 surface opposite the S4 surface. The interlayer film 3 is disposed between the first glass plate 1 and the second glass plate 2 so as to face the S2 surface and the S3 surface. The interlayer film 3 is an interlayer film composed of one layer (an interlayer film having a single layer configuration).
[0015] FIG. 2 shows a schematic cross-sectional view of another example of a vehicle window glass according to the present disclosure.
[0016] The vehicle window glass 11 in FIG. 2 is similar to the vehicle window glass 10 in FIG. 1, except that instead of the interlayer film 3 having a single layer structure in FIG. 1, the vehicle window glass 11 has an interlayer film 4 having a three-layer structure composed of layers 4A to 4C that constitute the interlayer film.
[0017] The vehicle window glass of the present disclosure is preferably made of lightweight laminated glass.
[0018] 1m of vehicle window glass 2 The mass per unit is preferably 3 kg to 9 kg, and more preferably 4 kg to 8 kg. [Interlayer] The interlayer film is composed of at least one layer, i.e., the interlayer film may have a single layer structure or a multi-layer structure.
[0019] The Young's modulus of all layers constituting the interlayer is 2.5 MPa to 200 MPa, preferably 10 MPa to 100 MPa, more preferably 20 MPa to 100 MPa, and particularly preferably 30 MPa to 75 MPa at 23° C. When the Young's modulus of all layers constituting the interlayer is 2.5 MPa to 200 MPa at 23° C., the bending rigidity of the laminated glass using the interlayer can be increased.
[0020] The overall bending rigidity of a laminated glass is correlated with the thickness of the glass sheets constituting the laminated glass and the Young's modulus of the interlayer film. Therefore, a vehicle window glass including an interlayer film having a low Young's modulus, such as the sound-insulating interlayer film used in conventional sound-insulating laminated glass, has a lower bending rigidity than a window glass not including an interlayer film having a low Young's modulus. Therefore, it is preferable that the interlayer film has a higher Young's modulus, regardless of the number of layers.
[0021] Furthermore, when the intermediate film has a multi-layer structure, each layer may have a different rigidity.
[0022] The method for measuring the Young's modulus of the interlayer film samples is detailed below.
[0023] The Young's modulus of the interlayer film samples was measured in accordance with JIS K 7161-1. This method aims to determine the tensile modulus of elasticity (Young's modulus) of the test specimen by measuring the force and elongation applied to the test specimen when it is pulled at a constant speed along the main axis (length direction) until the stress or strain (elongation) reaches a predetermined value.
[0024] The test machine used was a Tensilon universal testing machine (RTC-2410) manufactured by A&D Co., Ltd., which complies with JIS K 7161-1.
[0025] The test pieces were prepared by machining the interlayer film into a "tensile No. 5 dumbbell shape" conforming to JIS K 6251 by cutting.
[0026] The gauge length of the test piece was 33 mm.
[0027] The number of test pieces was one for each interlayer film.
[0028] The prepared test pieces were stored for 4 hours or more in an environment with a temperature of 23°C and a humidity of 40 to 60%.
[0029] The tensile tests were performed in an environment with a temperature of 23°C and a humidity of 40 to 60%, the same as when the samples were stored.
[0030] During the tensile test, the tensile test was performed without applying a preliminary force to the interlayer film sample.
[0031] The test speed during the tensile test was 0.33 mm / min, which is a speed that gives a strain of 1% of the gauge length per minute.
[0032] The stress applied to the test piece, σ [MPa], is calculated by multiplying the force F [N] applied during measurement by the initial cross-sectional area A [mm 2 ] was divided by this value.
[0033] The strain ε [-] generated in the test piece was calculated by dividing the increase in the gauge length of the test piece, ΔL0 [mm], by the gauge length of the test piece, L0 [mm].
[0034] The Young's modulus E [MPa] of the test specimen was calculated by dividing the difference between the stress σ2 [MPa] at the strain ε2 (0.25%) of the test specimen and the stress σ1 [MPa] at the strain ε1 (0.05%) of the test specimen by the difference between the strain ε2 of the test specimen and the strain ε1 of the test specimen.
[0035] The stress, Young's modulus, and strain in this test were reported to two significant figures.
[0036] The layers constituting the interlayer may be made of, for example, polyvinyl butyral (PVB), SentryGlas® (Dupon), polycarbonate, ionomer, polyethylene terephthalate (PET), or other suitable polymer or thermoplastic material, etc. Also, the layers constituting the interlayer are preferably made of a thermoplastic resin.
[0037] From the viewpoints of simplifying the production method and reducing the weight of the vehicle window glass, the interlayer film is preferably an interlayer film composed of one layer (an interlayer film having a single layer configuration).
[0038] The thickness of the interlayer is not particularly limited, but from the viewpoint of increasing the bending rigidity and penetration resistance of the laminated glass, it is preferably 0.3 mm to 3.0 mm, and more preferably 0.3 to 1.0 mm.
[0039] The method for producing the interlayer film in the present disclosure is not particularly limited, and any known method can be used. For example, the method for forming the interlayer film raw material resin into a film includes, but is not limited to, the usual extrusion method or calendar roll method. [First glass plate] The first glass sheet in the vehicle window glass of the present disclosure has not been subjected to a tempering treatment (i.e., it is non-tempered glass). Here, the tempering treatment refers to a treatment (including both physical tempering and chemical tempering) for increasing the strength by applying a compressive stress to the surface of the glass sheet.
[0040] When a tempered glass plate is used as the first glass plate (the glass plate on the vehicle exterior side) in a vehicle window glass, the chipping resistance is reduced due to tensile stress generated inside the glass.
[0041] The first glass plate is not particularly limited as long as it has not been subjected to a tempering treatment, and any known glass used for vehicle window glass (e.g., soda-lime glass, aluminosilicate glass, borosilicate glass, alkali-free glass, quartz glass, etc.) can be used. In order to adjust the optical properties of the glass plate, a coloring component such as Fe2O3, CeO2, TiO2, CoO, Cr2O3, NiO, or Se may be contained in an amount of up to 5 mass %.
[0042] The thickness of the first glass plate is 1.5 mm or less, preferably 0.3 mm to 1.5 mm, and more preferably 0.4 mm to 1.2 mm. [Second glass pane] The second glass plate in the vehicle window glass of the present disclosure may be a glass plate that has not been subjected to a tempering treatment, or may be a glass plate that has been subjected to a tempering treatment. The second glass plate is not particularly limited, and may be a known glass (e.g., soda-lime glass, borosilicate glass, alkali-free glass, quartz glass, physically tempered glass, chemically tempered glass, etc.) used in vehicle window glasses. In order to adjust the optical properties of the glass plate, a coloring component such as Fe2O3, CeO2, TiO2, CoO, Cr2O3, NiO, or Se may be contained in an amount of up to 5 mass %.
[0043] The thickness of the second glass plate is not particularly limited, but is preferably 0.3 mm to 1.7 mm, more preferably 0.55 mm to 1.5 mm, and further preferably 0.7 mm to 1.4 mm.
[0044] The manufacturing method (molding method) of the first glass plate and the second glass plate described above is not particularly limited, and any known manufacturing method (for example, a float method) can be used. [Functional layer] The vehicle window glass of the present disclosure may further include a functional layer between the first glass plate and the second glass plate.
[0045] The vehicle window glass of the present disclosure can be manufactured by a known method using the above-mentioned components. EXAMPLES
[0046] Examples of the present disclosure will be described below, but the present disclosure is not limited to the following examples. <Preparation of laminated glass samples> Glass plates having the thicknesses shown in Table 1 below were used as the first glass plate or the second glass plate.
[0047] As the interlayer film, the following interlayer film sample A1, A2 or A3 was used.
[0048] Interlayer film A1: A single-layer interlayer film (thickness 0.78 mm) made of PVB having a high Young's modulus. The Young's modulus at 23°C was 49 MPa.
[0049] Interlayer film A2: an interlayer film (thickness 0.85 mm) having a three-layer structure of a PVB layer having a low Young's modulus / a PVB layer having a low Young's modulus / a PVB layer having a low Young's modulus. The Young's modulus of each of the PVB layers having a low Young's modulus at 23° C. was 1.3 MPa.
[0050] Interlayer film A3: an interlayer film (thickness 0.86 mm) having a three-layer structure of a PVB layer having a high Young's modulus / a PVB layer having a low Young's modulus / a PVB layer having a high Young's modulus. At 23°C, the Young's modulus of the PVB layer having a high Young's modulus constituting interlayer film A3 was 49 MPa, and the Young's modulus of the PVB layer having a low Young's modulus was 1.1 MPa.
[0051] Ordinary laminated glass is produced by sandwiching one continuous interlayer film between two glass sheets, but in the manufacturing method of laminated glass for vehicles using a laminated interlayer film such as interlayer film A3, one PVB layer with a low Young's modulus is sandwiched between two PVB layers with high Young's modulus, and the laminated interlayer film is further sandwiched between two glass sheets.
[0052] In this case, the interfaces between the layers constituting the interlayer film become inconspicuous as the layers are fused together when the laminated glass for vehicles is heated and pressurized in an autoclave, and therefore do not obstruct the visibility of passengers.
[0053] Each interlayer sample was sandwiched between the first glass plate and the second glass plate, placed in a rubber bag, and suctioned under reduced pressure to remove any air remaining between the components. The deaerated laminate was then placed in an autoclave to perform preliminary bonding. At this time, the temperature was set to 90°C, the pressure to 0.25 MPa, and the temperature retention time was 30 minutes. Next, the autoclave temperature was set to 135°C, the pressure to 1.3 MPa, and the temperature retention time to 25 minutes to perform finish bonding, and the laminated glass was obtained by integrating the above laminated bodies.
[0054] The laminated glass samples produced are as shown in Table 1 below.
[0055] [Table 1]
[0056] In all the examples and comparative examples except Comparative Example 4 and Comparative Example 13, the first glass plate and the second glass plate were not subjected to a tempering treatment. Specifically, in all the examples and comparative examples except Comparative Example 4 and Comparative Example 13, the first glass plate and the second glass plate were obtained by forming soda-lime glass by the float method. The first glass plate in Comparative Example 4 and Comparative Example 13 is a chemically tempered aluminosilicate glass, and has a compressive stress layer on the S1 surface side (compressive stress 799 MPa, thickness 43.3 μm) and the S2 surface side (compressive stress 806 MPa, thickness 43.3 μm). The value of the compressive stress of the chemically tempered glass and the thickness of the compressive stress layer were obtained using a surface stress meter (Orihara Manufacturing Co., Ltd., FSM-6000LE) that uses the optical waveguide effect as the observation principle. <Chipping resistance test> As shown in Fig. 3, a silicon rubber sheet 31 (thickness 3 mm) with an opening of 150 mm x 150 mm in the center of a 300 mm x 300 mm size and a plywood board 32 (thickness 15 mm) were stacked, a test piece (laminated glass sample) 10A as a test specimen was placed on the silicon rubber sheet 31, and a Vickers diamond indenter 21 was dropped from a height h to examine chipping resistance. In order to make the indenter collide vertically with the test piece, a guide tube made of hard polyvinyl chloride was used as necessary. The test conditions were as follows.
[0057] Test conditions -Size of test piece (laminated glass): 300mm x 300mm Vickers diamond indenter: 8.5g (M0-MINDV, Nanovea) Test temperature: 23℃ Specifically, a Vickers diamond indenter was dropped freely onto the center of the first glass plate side of the laminated glass samples of the examples and comparative examples. The drop height h was started from 100 mm, and if the length of the radial cracks generated in the laminated glass sample was less than 10 mm, the drop position was changed, the drop height was increased by 100 mm each time, and the test was repeated. When the length of the radial cracks generated in the laminated glass sample exceeded 10 mm, it was defined as breakage, and the drop height of the Vickers diamond indenter at that time was recorded as the Break Height. For each example and comparative example, the test was performed 10 times to obtain the average value of the Break Height. Furthermore, the length of the cracks generated at the time of breakage (Break Length) was measured, and the average value was calculated.
[0058] The maximum drop height was 2000 mm. If the length of the radial crack was less than 10 mm even at a drop height of 2000 mm, the length of the crack at that point was recorded as the break length, and the break height was recorded as 2100 mm, and the average value was calculated.
[0059] The results are shown in Table 1 above. <Concentric bending test (rigidity evaluation)> A concentric bending test was carried out using the laminated glass samples of Examples 1 to 4 and Comparative Examples 5 to 12 having glass plates of the same thickness as the laminated glass samples. Specifically, as shown in Fig. 4, a load was gradually increased on a test piece (laminated glass sample) 10A using a support ring 13 and a load ring 14, and the amount of deflection against the load when it reached 500N was measured. An Instron material testing machine (Model 8871) was used as the testing machine. <Test conditions> -Size of test piece (laminated glass sample): 300mm x 300mm Load ring: diameter 50mm, radius of curvature 2.5mm Support ring: diameter 150mm, radius of curvature 2.5mm Crosshead speed: 1mm / min Load side: First glass plate side Test temperature: 23℃ The results are shown in Table 1 above. <Mass per unit area> 1m of the laminated glass sample 2 The mass per unit area was measured.
[0060] The results are shown in Table 1 above.
[0061] The results shown in Table 1 show that the laminated glass samples of Examples 1 to 4 have a larger average break height and a smaller average break length than the laminated glass samples of Comparative Examples 1 to 13, and therefore have higher chipping resistance.
[0062] In Comparative Examples 1-3, the same interlayer film A1 as in Examples 1-4 was used, but the thickness of the first glass plate exceeded 1.5 mm and the chipping resistance was inferior to that of Examples 1-4.
[0063] In Comparative Examples 5 to 8, the thickness of the first glass plate was 1.5 mm or less, as in Examples 1 to 4. However, the Young's modulus at 23°C of all layers constituting the interlayer was less than 2.5 MPa, and the chipping resistance was inferior to that of Examples 1 to 4.
[0064] In Comparative Examples 9 to 12, the thickness of the first glass plate was 1.5 mm or less, as in Examples 1 to 4. However, the Young's modulus at 23°C of some of the layers constituting the interlayer was less than 2.5 MPa, and the chipping resistance was inferior to that of Examples 1 to 4.
[0065] In Comparative Examples 4 and 13, the thickness of the first glass plate was 1.5 mm or less as in Examples 1 to 4, and the same interlayer film A1 was used as in Examples 1 to 4. However, the first glass plate was tempered, and the chipping resistance was significantly inferior to that of Examples 1 to 4. In Table 1, ">300" listed as the average value of the break length in Comparative Examples 4 and 12 indicates that it exceeds 300 mm.
[0066] Moreover, it was found that the laminated glass samples of Examples 1 to 4 had smaller deflections when a constant load was applied in a concentric bending test than the laminated glass samples of Comparative Examples 5 to 12 having glass plates of the same thickness, and thus had superior rigidity.
[0067] Furthermore, the laminated glass samples of Examples 1 to 4 were 1 m 2 The mass per unit was found to be lightweight, ranging from 4.8 to 6.2 kg.
[0068] From the above, it was found that the laminated glass samples of Examples 1 to 4 were lightweight and had excellent rigidity and chipping resistance, and were suitable for use as window glass for vehicles. [Explanation of symbols]
[0069] 1 First glass plate 2. Second Glass Pane 3, 4 Interlayer 4A, 4B, 4C Layers that make up the interlayer S1 S1 side S2 S2 side S3 S3 surface S4 S4 surface 10, 11 Vehicle window glass 10A Laminated Glass Sample 13 Support Ring 14 Load Ring 21 Vickers diamond indenter h Drop height of Vickers diamond indenter 31 Silicone rubber sheet 32 Plywood
Claims
1. A first glass plate having an S1 surface facing the outside of a vehicle and an S2 surface opposite to the S1 surface; A second glass plate having an S4 surface facing the interior side of the vehicle and an S3 surface opposite to the S4 surface; an interlayer film including at least one layer disposed between the first glass plate and the second glass plate and facing the S2 surface and the S3 surface; A vehicle window glass comprising: The intermediate film does not contain silica particles, The Young's modulus of all layers constituting the interlayer is 10 MPa to 200 MPa at 23° C., The first glass plate and the second glass plate are not subjected to a tempering treatment, The first glass plate has a thickness of 0.4 mm to 1.2 mm.
2. 2. The vehicle window glass according to claim 1, wherein the Young's modulus of all layers constituting the interlayer film is 10 MPa to 100 MPa at 23° C.
3. 3. The vehicle window glass according to claim 1, wherein the second glass plate has a thickness of 0.3 mm to 1.7 mm.
4. The vehicle window glass according to any one of claims 1 to 3, wherein the interlayer film is an interlayer film constituted by one layer.
5. A first glass plate having an S1 surface facing the outside of a vehicle and an S2 surface opposite to the S1 surface; A second glass plate having an S4 surface facing the interior side of the vehicle and an S3 surface opposite to the S4 surface; an interlayer film consisting of one layer, the interlayer film being disposed between the first glass plate and the second glass plate and facing the S2 surface and the S3 surface; A vehicle window glass comprising: The intermediate film does not contain silica particles, The Young's modulus of the interlayer is 10 MPa to 50 MPa at 23° C., The first glass plate and the second glass plate are not subjected to a tempering treatment, The first glass plate has a thickness of 0.4 to 1.2 mm; The thickness of the second glass sheet is 0.7 mm to 1.4 mm. Vehicle window glass.
Citation Information
Patent Citations
Passivated biologically active substance, affinity chromatography and drug for self immunological disease diagnosis and / or therapy
JP1983090518A
High-rigidity intermediate layer and lightweight laminated multilayer panel
JP2015516934A
lightweight composite laminated glass
JP2016530190A
Glass laminate structure with improved edge strength
JP2016539890A
Reinforced glass and its composition
JP2017520496A